Investigation of directly suspended droplet micro extraction method for extraction of trihalomethane and halomethane in water samples - Seyed Kamal Rajabi; Ahmad Nikserasht (Egyptian Journal of Petroleum)
Simple and efficient directly suspended droplet micro extraction (DSDME) in conjunction with gas chromatography-electron capture detector (GC-ECD) has been developed for extraction and determination of Halomethane and Trihalomethane from water samples. In this technique a micro drop of n-hexane is delivered to the surface of an aqueous sample while being agitated by a stirring bar in the bulk of solution. Factors relevant to the extraction efficiency were studied and optimized. The optimized extraction conditions were extraction solvent: n- hexane; NaCl concentration: 1 M; solvent extraction volume: 50 μL; stirring rate: 720 rpm and the extraction time: 5 min. The detection limits of the method were in the range of 0.059–0.137 µg L−1, relative standard deviation (n = 3) range were 0.019–0.048%. A good linearity (r2 ≥ 0.997) and a relatively broad dynamic linear range (10–200 µg L−1) were obtained and recoveries of method were in the range of 97.69–99.51%. Finally, the proposed method was successfully utilized for pre concentration and determination of halo methane in different real samples. Successfully DSDME technique combined with capillary GC-ECD for the analysis of THMs and HMs in the water investigated samples. Keywords: Tri halo methane, Gas chromatography, Water analysis